2020
DOI: 10.3390/app10196991
|View full text |Cite
|
Sign up to set email alerts
|

Field-Applicable Pig Anomaly Detection System Using Vocalization for Embedded Board Implementations

Abstract: Failure to quickly and accurately detect abnormal situations, such as the occurrence of infectious diseases, in pig farms can cause significant damage to the pig farms and the pig farming industry of the country. In this study, we propose an economical and lightweight sound-based pig anomaly detection system that can be applicable even in small-scale farms. The system consists of a pipeline structure, starting from sound acquisition to abnormal situation detection, and can be installed and operated in an actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Attempts have been made to detect posture [ 18 ] and count each pig within a pen [ 20 ] using deep learning. This technology allows for improved management of health issues in pigs [ 22 , 23 , 24 , 26 ]. More sophisticated methods have been introduced to address pig monitoring issues [ 27 , 31 , 32 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have been made to detect posture [ 18 ] and count each pig within a pen [ 20 ] using deep learning. This technology allows for improved management of health issues in pigs [ 22 , 23 , 24 , 26 ]. More sophisticated methods have been introduced to address pig monitoring issues [ 27 , 31 , 32 ].…”
Section: Related Workmentioning
confidence: 99%
“…Thus, managing each pig individually to their health and welfare needs is not an easy task. To reduce management workload, many studies have reported the use of surveillance techniques to address health and welfare problems [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Therefore, the use of object detection [ 37 ] to detect pigs by means of a surveillance camera can reduce the management workload within a pig pen.…”
Section: Introductionmentioning
confidence: 99%
“…Early methods used statistical classification [ 30 ], DTW distance [ 31 ], and discriminant analysis [ 32 ] to classify selected dog behaviors, providing proof of concept. Later, with the improvement in machine learning techniques and the increase in their popularity in different fields of research [ 36 , 38 , 39 , 40 ], more methods have been employed to recognize dog behaviors. For instance, Chambers et al [ 34 ] aimed to validate dog behavior recognition, with a focus on eating and drinking, using FilterNet and a large crowd-sourced dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have been conducted on automatic livestock monitoring using various methods. Some of these include wearable sensor-based [ 6 , 7 , 8 ], audio-based [ 9 , 10 , 11 , 12 , 13 ], or video-based methods [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Compared with sensor-based methods, video-based methods can provide a non-invasive, non-stressful, and intuitive way to monitor the behavior of an individual or a group of pigs where the sensor-based method fail to do.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with audio-based methods, video-based methods can intuitively grasp a pig’s health condition. In contrast, specialists are always required for further sound analysis and recognition in audio-based methods [ 9 , 10 , 11 ]. Thus, video-based methods have received the most attention in recent studies.…”
Section: Introductionmentioning
confidence: 99%